Impact of Different Ventilation Strategies on Driving Pressure, Mechanical Power, and Biological Markers During Open Abdominal Surgery in Rats. (October 2017) - Maia, Lígia de A.; Samary, Cynthia S.; Oliveira, Milena V.; Santos, Cintia L.; Huhle, Robert; Capelozzi, Vera L.; Morales, Marcelo M.; Schultz, Marcus J.; Abreu, Marcelo G.; Pelosi, Paolo; Silva, Pedro L.; Rocco, Patricia Rieken Macedo
Abstract : BACKGROUND: Intraoperative mechanical ventilation may yield lung injury. To date, there is no consensus regarding the best ventilator strategy for abdominal surgery. We aimed to investigate the impact of the mechanical ventilation strategies used in 2 recent trials (Intraoperative Protective Ventilation [IMPROVE] trial and Protective Ventilation using High versus Low PEEP [PROVHILO] trial) on driving pressure ( ΔP RS ), mechanical power, and lung damage in a model of open abdominal surgery. METHODS: Thirty-five Wistar rats were used, of which 28 were anesthetized, and a laparotomy was performed with standardized bowel manipulation. Postoperatively, animals (n = 7/group) were randomly assigned to 4 hours of ventilation with: (1) tidal volume ( V T ) = 7 mL/kg and positive end-expiratory pressure (PEEP) = 1 cm H2 O without recruitment maneuvers (RMs) (low V T /low PEEP/RM−), mimicking the low- V T /low-PEEP strategy of PROVHILO; (2) V T = 7 mL/kg and PEEP = 3 cm H2 O with RMs before laparotomy and hourly thereafter (low V T /moderate PEEP/4 RM+), mimicking the protective ventilation strategy of IMPROVE; (3) V T = 7 mL/kg and PEEP = 6 cm H2 O with RMs only before laparotomy (low V T /high PEEP/1 RM+), mimicking the strategy used after intubation and before extubation in PROVHILO; or (4) V T = 14 mL/kg and PEEP = 1 cm H2 O without RMs (high V T /low PEEP/RM−), mimicking conventional ventilation used in IMPROVE. Seven rats were not tracheotomized, operated, or mechanically ventilated, and constituted the healthy nonoperated and nonventilated controls. RESULTS: Low V T /moderate PEEP/4 RM+ and low V T /high PEEP/1 RM+, compared to low V T /low PEEP/RM− and high V T /low PEEP/RM−, resulted in lower ΔP RS (7.1 ± 0.8 and 10.2 ± 2.1 cm H2 O vs 13.9 ± 0.9 and 16.9 ± 0.8 cm H2 O, respectively; P < .001) and less mechanical power (63 ± 7 and 79 ± 20 J/min vs 110 ± 10 and 120 ± 20 J/min, respectively; P = .007). Low V T /high PEEP/1 RM+ was associated with less alveolar collapse than low V T /low PEEP/RM− ( P = .03). E-cadherin expression was higher in low V T /moderate PEEP/4 RM+ than in low V T /low PEEP/RM− ( P = .013) or high V T /low PEEP/RM− ( P = .014). The extent of alveolar collapse, E-cadherin expression, and tumor necrosis factor-alpha correlated with ΔP RS ( r = 0.54 [ P = .02], r = −0.48 [ P = .05], and r = 0.59 [ P = .09], respectively) and mechanical power ( r = 0.57 [ P = .02], r = −0.54 [ P = .02], and r = 0.48 [ P = .04], respectively). CONCLUSIONS: In this model of open abdominal surgery based on the mechanical ventilation strategies used in IMPROVE and PROVHILO trials, lower mechanical power and its surrogate ΔP RS were associated with reduced lung damage. Abstract : Supplemental Digital Content is available in the text.Published ahead of print July 27, 2017.